2015
DOI: 10.1111/psj.12132
|View full text |Cite
|
Sign up to set email alerts
|

Institutions, Incentives, and Policy Entrepreneurship

Abstract: Policy entrepreneurship is often used to explain agenda setting through reference to the behavior of individual "change agents." But there are still gaps in our understanding of what motivates entrepreneurs. Rational choice theory emphasizes the importance of material and nonmaterial incentives; however, it remains unclear what role institutions play. This article aims to empirically examine the relationship between incentives and institutional encouragement of innovation. Using a case study of the federal gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…These other studies’ results tended to find that including a variety of rewards was the best strategy if rewards were necessary (Bessonova & Gonchar, 2017 ; Cordero et al, 2005 ; Maria Stock et al, 2017 ). Curran and Walsworth ( 2014 ) found that it was sometimes possible to increase innovation with compensation, but only with the correct compensation, which connects to the arguments of Hopkins ( 2016 ), who calls for material, communal, or related incentives to foster innovative behavior. Hartmann ( 2006 ) analogously found that the major predictor of the efficacy of rewards was having a variety of rewards, findings echoed in those of other studies (Amabile, 1997 ; Cordero et al, 2005 ; Hopkins, 2016 ).…”
Section: Results For Perceived Values: What Makes Innovation Worth Domentioning
confidence: 85%
See 1 more Smart Citation
“…These other studies’ results tended to find that including a variety of rewards was the best strategy if rewards were necessary (Bessonova & Gonchar, 2017 ; Cordero et al, 2005 ; Maria Stock et al, 2017 ). Curran and Walsworth ( 2014 ) found that it was sometimes possible to increase innovation with compensation, but only with the correct compensation, which connects to the arguments of Hopkins ( 2016 ), who calls for material, communal, or related incentives to foster innovative behavior. Hartmann ( 2006 ) analogously found that the major predictor of the efficacy of rewards was having a variety of rewards, findings echoed in those of other studies (Amabile, 1997 ; Cordero et al, 2005 ; Hopkins, 2016 ).…”
Section: Results For Perceived Values: What Makes Innovation Worth Domentioning
confidence: 85%
“…Support was a consistent consideration of research examining strategies that build expectancies and confidence to innovate (e.g., Kuznetsov & Kuznetsova, 2011 ). Common supports identified included creating a conducive innovation climate or culture (Dee et al, 2002 ; Hopkins, 2016 ; Kung & Chao, 2019 ; Montani et al, 2014 ; Susha et al, 2015 ), having reliable infrastructure (Susha et al, 2015 ), availability of mentoring (Apergis & Pekka-Economou, 2010 ), and inviting folks to engage with groups pursuing innovation (Apergis & Pekka-Economou, 2010 ; Curado et al, 2018 ; Messmann & Mulder, 2014 ; Radicic, Pugh, Hollanders, Wintjes, & Fairburn, 2016 ; Susha et al, 2015 ). Explicitly modelling flexibility and exploration (Amabile, 1997 ; Hartmann, 2006 ; Montani et al, 2014 ; Sorice & Donlan, 2015 ), breaking a task down into smaller, manageable pieces (Dietrich et al, 2016 ; Pihie, 2007 ), and providing ample time and financial resources (Aarikka-Stenroos et al, 2017 ; Hartmann, 2006 ; Hosseini & Narayanan, 2014 ; Ozorhon & Oral, 2017 ) were also found to be crucial supports for confidence to innovate.…”
Section: Results For Expectancies In the Literature: Can I Do This?mentioning
confidence: 99%
“…This is being coordinated through institutions such as, government, legal system, educational structure, labour market and media, among others (Knight, 2016). Even though the influence of structural powers supported in institutions has been studied in the context of entrepreneurship (Bjørnskov & Foss, 2016;Gohmann, 2012;Hopkins, 2016) and informal entrepreneurship (Dau & Cuervo-Cazurra, 2014b), there is still a lack of understanding on the challenges related to structural powers experienced by certain groups and their intersecting identities in facilitating or constraining their entrepreneurial initiatives (McBride, Hebson, & Holgate, 2014;Mulinari & Selberg, 2013;Zander, Zander, Gaffney, & Olsson, 2010). Moreover, intersectionality has not been used extensively to study the impact of s tructures of discrimination and systems of p ower and i nequality in entrepreneurial endeavours (Rodriguez, Holvino, Fletcher, & Nkomo, 2016).…”
Section: Intersectionality and Its Application In Entrepreneurshipmentioning
confidence: 99%
“…Scholars have identified PEs in the bureaucracy (Arnold, 2015;Hopkins, 2015) as well as being more elite players in the policy process (Kingdon, 2002;Mintrom, 1997a;Palmer, 2015;Zahariadis, 2014). PEs can be found both within and outside of government.…”
Section: Policy Entrepreneursmentioning
confidence: 99%
“…In a thorough review of PE literature, Jones et al (2016) found three main factors to be associated with the success of policy entrepreneurs: resources (e.g., knowledge, time and money), access to decision makers, and strategy (e.g., issue framing). It is when these three factors are aligned that PEs have been shown to be causal mechanisms for agenda setting (Hopkins, 2015;Huitema et al, 2011;Mintrom, 1997a).…”
Section: Policy Entrepreneursmentioning
confidence: 99%